Information literacy of managers: models and factors - Bolek, Vladimír; Kokles, Mojmír; Romanová, Anita; Zelina, Michal (Journal of Business Economics and Management, 2018)
Participation in the information society means faster communication, development of new ideas, more creative ideas and education in terms of lifelong learning. The information society is a reality and a dominant element of politics in all developed countries of the world. Information literacy deals with the human ability to work effectively in the information society. Information literacy needs to be understood in a wider context, rather than only in terms of IT skills and abilities. The article compares and defines the concept of information literacy. It compares selected information literacy models. The starting point is a survey conducted among business managers in the Slovak Republic examining the level of information literacy of managers. The findings identify factors affecting the aggregate index of information literacy of managers and the proposed quantitative and qualitative model of the information literacy of managers. Presented are the unique results of long-term research on information and digital literacy in the Slovak Republic (Central Europe, the European Union and V4-Visegrad countries). So far, no research has been conducted focusing on the level of digital literacy of business managers and an information literacy model that would contribute to raising their level.